Experimental design for tri-state logic - Mallik, Hari Shankar; Rijal, Ramesh; Lamichhane, Hari Prasad (Himalayan Physics, 2023)
Tri-State Logic device effectively connects many devices into the same data line for data transfer. The Tri- State TTL inverter has three output states such as LOW, HIGH, and open or high-impedance (High-Z) states. The High-Z state either electrically isolates the devices from the data transmission line or connects them one at a time to the data transmission line. The measurement of the floating output (opened or disconnected) state is a challenging task. This issue can be resolved by introducing a potential divider into the output of the original Tri-State TTL inverter circuit and making it possible for a lab experiment